Effects of the theory of didactical situations' application in mathematics education: A metasynthesis - Julius Ceasar Hortelano; Maricar Prudente (Journal of Pedagogical Research, 2024)
Conceptualized in France during the sixties, the Theory of Didactical Situations [TDS] is a pivotal framework for developing mathematics teaching and learning processes. Despite the increasing qualitative studies over the last ten years, there remains a dearth of analysis of its effects on mathematics education. Through a Grounded Formal Theory approach, this paper presents the metasynthesis of 28 studies screened from four research databases- ProQuest, EBSCO, SCOPUS, and JSTOR. Data extraction was performed to enumerate the author/s, country, publication year, and connected theoretical approaches with TDS. Subsequently, the studies were categorized into three axial codes based on the studies' goals of applying TDS: lesson sequence, teacher development, and learning innovations. The synthesis underscores TDS' capacity to improve the sequence of mathematics lessons, particularly geometry and number patterns; develop teachers' pedagogical practices in teaching elementary, high school, and college students; and be a practical tool in innovating didactical resources for learning mathematics. TDS was also associated with other theoretical approaches, such as constructivism, realistic mathematics education, gamification, and technology-based instruction. Most of these effects were rooted in the challenges experienced during the COVID-19 pandemic and the adaptation of TDS to the digital era, including distance and online learning. While the European and Western Asian countries have been at the forefront of TDS integration, the paper advocates for broader global adoption of this theory to enrich mathematics education worldwide.